Question
upstudy study bank question image url

\( \begin{array}{ll}\text { (c) }-2^{x}=-16 & \text { (t) }-2^{x}=-32 \\ \text { (ii) }-2^{x}=-1 & \text { (i) } 7^{x}=49 \\ \text { (k) } 7^{x}=1 & \text { (l) } 3^{2 x}=81 \\ \text { (ii) } 10^{10 x}=100 & \text { (o) } 4^{x}=2 \\ \text { (4) } 25^{x}=125 & \text { (r) } 9^{3 x}=27^{x} \\ \text { (t) } 9^{3 x-1}=27 & \text { (u) } 16^{2 x}=4^{x-1}\end{array} \)

Ask by Griffiths Burton. in South Africa
Feb 26,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

Here are the solutions for each equation: - (c) \( x = 4 \) - (t) \( x = 5 \) - (ii) \( x = 0 \) - (i) \( x = 2 \) - (k) \( x = 0 \) - (l) \( x = 2 \) - (ii) \( x = 0.2 \) - (o) \( x = 0.5 \) - (4) \( x = 1.5 \) - (r) \( x = 0 \) - (t) \( x = 0.833... \) (or \( \frac{5}{6} \)) - (u) \( x = -0.333... \) (or \( -\frac{1}{3} \))

Solution

Below are one acceptable set of solutions. In each case we assume that, for example,   –2ˣ means –(2ˣ) rather than (–2)ˣ. • (c) –2ˣ = –16   Add a minus sign to both sides: 2ˣ = 16   Since 16 = 2⁴, we have 2ˣ = 2⁴ so x = 4. • (t) –2ˣ = –32   Then 2ˣ = 32, and 32 = 2⁵ so x = 5. • (ii) –2ˣ = –1   Then 2ˣ = 1. Since 2⁰ = 1, we have x = 0. • (i) 7ˣ = 49   Write 49 as 7² so that 7ˣ = 7²; hence x = 2. • (k) 7ˣ = 1   Since 7⁰ = 1, it follows that x = 0. • (l) 3^(2x) = 81   Notice that 81 = 3⁴. Therefore 3^(2x) = 3⁴ implying 2x = 4 and so x = 2. • (ii) 10^(10x) = 100   Write 100 as 10². Then 10^(10x) = 10² so 10x = 2 and x = 0.2. • (o) 4ˣ = 2   Write 4 as 2² so that 4ˣ = (2²)ˣ = 2^(2x). Hence the equation becomes 2^(2x) = 2¹, so 2x = 1 and x = ½. • (4) 25ˣ = 125   Express 25 = 5² and 125 = 5³. The equation becomes (5²)ˣ = 5³, i.e. 5^(2x) = 5³. Thus, 2x = 3 and x = 1.5 (or 3/2). • (r) 9^(3x) = 27^(x)   Write 9 = 3² and 27 = 3³. Then    9^(3x) = (3²)^(3x) = 3^(6x)    27^(x) = (3³)^(x) = 3^(3x).   So 3^(6x) = 3^(3x) which implies 6x = 3x, hence 3x = 0 and x = 0. • (t) 9^(3x–1) = 27   Again, 9 = 3² and 27 = 3³. Rewrite the left side:    9^(3x–1) = (3²)^(3x–1) = 3^(2(3x–1)) = 3^(6x–2).   Thus 3^(6x–2) = 3³, so 6x – 2 = 3, giving 6x = 5 and x = 5/6. • (u) 16^(2x) = 4^(x–1)   Write 16 as 4² so that:    16^(2x) = (4²)^(2x) = 4^(4x).   Then the equation becomes 4^(4x) = 4^(x–1). Equate exponents: 4x = x – 1, so    4x – x = –1 → 3x = –1, hence x = –1/3. Thus, the answers are:   (c) x = 4   (t) x = 5   (ii) x = 0    [for –2ˣ = –1]   (i) x = 2   (k) x = 0   (l) x = 2   (ii) x = 0.2  [for 10^(10x) = 100]   (o) x = 1/2   (4) x = 3/2   (r) x = 0   (t) x = 5/6   (u) x = –1/3 Any answer set equivalent to these is correct.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To solve equations like these efficiently, remember the importance of understanding exponents. When you have equations where the base is the same, you can equate the exponents directly. For instance, in \(7^{x} = 49\), since \(49\) is \(7^2\), you can set \(x = 2\). It's that straightforward when bases match up! A common mistake many make is neglecting negative bases or forgetting to check the validity of solutions. For instance, in \(-2^{x} = -16\), one might mistakenly focus solely on the exponential form without realizing the negative sign affects how we interpret \(x\). Always keep track of signs when solving, and remember, extraneous solutions can creep in during the manipulation, particularly when working with even roots. Happy solving!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy